Key performance indicators for start-ups in furniture industry - Guoda Kirjazovaitė (Mokslas: Lietuvos Ateitis, 2024)
It is not uncommon to see start-ups suddenly fail. Often, startups try to follow the example of other, successful companies, but they don’t always succeed, so this article looks at KPIs for startups in the furniture industry. The furniture industry in the Baltic States is reviewed and their development at different stages of the company’s growth is analyzed. The product factors and interrelationships of a successful furniture company have been identified. The article presents the results of the surveyed companies engaged in the development of products for the furniture industry. The reasons and the main factors influencing the success of the company are given. Based on the results of the study, a model for the development of KPIs for start-ups in the furniture industry is presented and conclusions and suggestions are presented. The model consisted of 10 different spheres (success factors, fail factors, inbound logistics, outbound logistics, marketing & sales, procurement, operation, service, HRM, technology development, sustainability) for 5 different companies size (1–9 employees, 10–49 employees, 50–99 employees, 100–249 employees and 250 and more employees). In the model were overwide main KPIs blocks and suggested considerate of companies size.